Creating knowledge-based healthcare organizations - Wickramasinghe, Nilmini.; Gupta, Jatinder N. D.; Sharma, Sushil K. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
This book brings together high quality concepts closely related to how knowledge management can be utilized in healthcare. It includes the methodologies, systems, and approaches needed to create and manage knowledge in various types of healthcare organizations. Furthermore, it has a global flavor, as we discuss knowledge management approaches in healthcare organizations throughout the world. For the first time, many of the concepts, tools, and techniques relevant to knowledge management in healthcare are available, offereing the reader an understanding of all the components required to utilize knowledge.